A Case Report : Sacrococcygeal Teratoma - Mangal, Abdul Baser; Walizada, Samsoor (International Journal For Research In Health Sciences And Nursing, 2020)
Sacrococcygeal teratomas (SCT) are tumors that arise in the sacrococcygeal area containing tissue from all three germ layers. SCT has an incidence of approximately one in 35,000 – 40,000 live births with malignant transformation with increasing age. We report a case in a 20 day old which was excised completely via the post anal route with no operative or postoperative morbidity.Sacrococcygeal teratoma (SCT) is the most common tumor presenting at birth. Commonly seen in female fetuses; this case presented, more or less with the whole feature of typical sacrococcygeal teratoma.